PENGARUH PENDIDIKAN KESEHATAN PHBS TATANAN SEKOLAH TERHADAP TINGKAT PENGETAHUAN DAN PERILAKU SISWA MI MA’HAD ISLAMY PURBAYAN KOTAGEDE YOGYAKARTA - Suyatno Suyatno (STIKes Surya Global Yogyakarta, 2017)
Background: The realization of community health can be achieved, if there program of Clean and Healthy Behavior (PHBS). The PHBS program is an effort to provide a learning experience or create a condition for individuals, families, groups and communities, by opening lines of communication, providing information and educating, to improve knowledge, attitude and behavior through leadership approach (Advocacy) Social support, and Empowerment. Objective: To know the effect of giving health education education about PHBS (school order) to knowledge in 4th and 5th grade students in MI Ma'ahad Islamy Purbayan Kotagede Yogyakarta. Method: The research was a type of quantitative research with experimental research type with the design used pre experimental one group pretest-posttest design, that was examining the causal relationship in the intervention group without using control comparator. The population of this research were MI Ma'ahad Islamy students as many as 32 students, class IV were 13 students, and class V were 19 students. The sampling technique in this research used saturated sampling that was sampling technique when all member of population used as sample. Result: Based on the result of data normality test by using skewnes method got the result of data below 0,05 meaningful of abnormal research data, skewness test pre test Free larva value p=0,01 (p0,005) Ho was rejected meaning abnormal data distribution . Skewnes test pre test eating canteen school value p=0.00 (p0.005) the Ho was rejected means the distribution of data was not normal. Skewness test pre test BAK BAB value p=0.00 (p0.005) Ho was rejected means the spread abnormal data. Test skewnes post test Wash hands before eating value p=0.00 (p0.005) Ho was rejected means the distribution of abnormal data. Test skewnes pre-test waste in garbage p value=0.00 (p0.005) Ho was rejected means the distribution of abnormal data. Based on the result of difference test in get result P value unpair was 0,002, because p value 0,05 Ho was rejected. It means that, knowledge and behavior before counseling PHBS there were differences before and after counseling. Conclusion: There is influence of knowledge and behavior before counseling PHBS with after counseling